Anatomical and histological changes in the spleen of post hatching indigenous chicken in Iraq: Ali Faris Reshag and Rabab Adnan Hamza - Hamza, Rabab Adnan (The Iraqi Journal of Veterinary Medicine, 2018)
The structure of the indigenous chickens spleen during the post-hatching period was determined by gross and light microscopical examination by using Hematoxylin and eosin and Massons Trichrome staining techniques. At one day old chicks the spleen was rounded in shape, pink in color. At two weeks old chicks the spleen was triangular in shape. At the progress of the aged the color of spleen became red-brown. In all ages the spleen consisted of white pulp and red pulp which were fused together. The spleen was encapsulated by thin connective tissue capsule contain few smooth muscles, the trabiculi were rare and thin. The red pulp consisted of venous sinuses surrounded by lymphatic cords. The white pulp consisted of peri-artery lymphoid sheath, peri-venous lymphoid sheath, peri ellipsoid lymphoid sheath, and Lymphatic follicles. The appearance of these elements was age dependant. At the first week of age the peri-artery lymphoid sheath and peri-venous lymphoid sheath were developed. At the third week, the peri ellipsoid lymphoid sheath, Lymphatic follicles were noticed and the plasma cells were scattered in the white pulp in addition to the lymphocytes. At one month of age, the germinal center appeared in some lymphatic follicle. The present study revealed that the spleen was well developed lymphatic organ at the age of three weeks.